(untitled) (International journal of medical sciences, 2026)
Benign prostatic hyperplasia (BPH) is one of the most prevalent urological conditions affecting aging men and represents a major cause of lower urinary tract symptoms (LUTS). Surgical intervention is indicated when conservative and pharmacological treatments fail. Traditionally, transurethral resection of the prostate (TURP) has been considered the surgical gold standard for moderate-sized prostates, while open prostatectomy (OP) has been reserved for large glands. Over the past two decades, holmium laser enucleation of the prostate (HoLEP) has emerged as a minimally invasive, size-independent alternative. This systematic review evaluates and compares HoLEP, TURP, and OP in terms of efficacy, safety, perioperative outcomes, long-term durability, and complications. Current evidence suggests that HoLEP provides equivalent or superior functional outcomes with reduced morbidity and retreatment rates, positioning it as a preferred surgical option for BPH when expertise is available.